Problematika dalam Penyidikan Perkara Tindak Pidana Korupsi - Nurholidah, Nurholidah; Lasmadi, Sahuri; Monita, Yulia (PAMPAS: Journal of Criminal Law, 2021)
This article aims to find out how the investigation into criminal acts of corruption was carried out by the Tanjung Jabung Timur Police investigators, and what were the obstacles in additional investigations to fulfill P-19. The method used is empirical juridical, examining the gap between das sollen and das sein. The results; First, the investigator on corruption at the Tanjung Jabung Timur Police in carrying out additional investigations to fulfill P-19 found various obstacles so the investigator passed the 14-day deadline specified in Article 138 (2) of the Criminal Procedure Code. Second, these obstacles are, the schedule of expert examinations is determined by the appointed expert, the witness does not fulfill the summons of the investigator, the presence of witnesses and experts outside the province, the address of the witness is difficult to find. Suggestions: 1) Investigators should be more careful in examining case file before it is submitted to the public prosecutor so that it can run effectively, efficiently, and giving satisfaction to the public, 2) KUHAP should be revised as soon as possible, especially regarding the 14-day period for investigators to correct the case file because in finding evidence is very unlikely to be done within 14 days and the Criminal Procedure Code can regulate the legal consequences for investigators who violate the provisions of Article 138 (2) of the Criminal Procedure Code. Â  ABSTRAK Artikel ini bertujuan untuk mengetahui bagaimana penyidikan terhadap tindak pidana korupsi yang dilakukan penyidik Polri Polres Tanjung Jabung Timur, dan apa saja kendala dalam penyidikan tambahan untuk pemenuhan P-19. Metode yang digunakan adalah yuridis empiris, yaitu mengkaji mengenai kesenjangan antara das sollen dengan das sein. Hasil penelitian ini; pertama, penyidik tipikor Polres Tanjung Jabung Timur dalam melakukan penyidikan tambahan untuk memenuhi P-19 menemukan berbagai kendala sehingga penyidik melewati batas waktu 14 hari yang sudah ditentukan dalam Pasal 138 Ayat (2) KUHAP. Kedua, kendala tersebut yaitu, jadwal pemeriksaan ahli ditentukan oleh ahli yang ditunjuk, saksi tidak memenuhi panggilan penyidik, keberadaan saksi dan ahli diluar provinsi, alamat saksi sulit ditemukan. Saran: 1) Penyidik harus lebih teliti memeriksa berkas perkara sebelum diserahkan kepada penuntut umum agar dapat berjalan dengan efektif, efisen, dan memberikan kepuasan kepada masyarakat, 2) KUHAP secepatnya direvisi khususnya mengenai rentang waktu 14 hari bagi penyidik untuk memperbaiki berkas perkara karena dalam menemukan bukti-bukti sangat tidak dimungkinkan dapat dilakukan dalam waktu 14 hari tersebut dan KUHAP dapat mengatur mengenai akibat hukum bagi penyidik yang melanggar Â ketentuan Pasal 138 Ayat (2) KUHAP.